The Influence of Electronic Word of Mouth and Digital Marketing on Decisions to Purchase Hotel Tickets Through Traveloka Applications (Case Study of Consumers in the City of Bandung) - Andhi Sukma; Riska Riska (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
This study aims to determine and analyze the effect of electronic Word of Mouth (e-WOM) and Digital Marketing on the decision to purchase hotel tickets through the Traveloka application. This research was conducted with a quantitative approach. Primary data collection was carried out by distributing questionnaires to a sample of 100 customers in the city of Bandung, and. The data analysis used in this study is a multiple linear regression test. The results showed that partially e-WOM and Digital Marketing had a positive and significant influence on purchasing decisions, e-WOM with a significance level of trust of 0.003 <0.05, Digital Marketing of 0.000 <0.05, . e-WOM and Digital Marketing simultaneously have a positive and significant effect on purchasing decisions. From the determination test it is known that the percentage of influence. e-WOM and Digital Marketing of 0.627 or 62.70%, meaning that the variables are e-WOM and Digital Marketing, while the remaining 37.3% is influenced by other variables outside of this study.